2018
DOI: 10.1021/acs.bioconjchem.8b00305
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like Surface of Three-Metal-Component Layered Double Hydroxide Composites for Improved Antibacterial Activity of Lysozyme

Abstract: Microbes play an important function in our lives, while some pathogenic bacteria are responsible for many infectious diseases, food safety, and ecological pollution. Layered double hydroxide (LDH) is a kind of natural two-dimensional material and has been applied in many fields. Lysozyme is a green natural antibacterial agent, while the antimicrobial activity of lysozyme is not as good as antibiotics. We use a different ratio of cations to tune the morphology of LDH covered with lysozyme to enhance the antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…The thermal stability and antibacterial activity against some clinically important bacterial pathogens, namely Bacillus subtilis , Pseudomonas aeruginosa , Staphylococcus aureus , and Escherichia coli was proven for a polyacrylonitrile/Zn-Al LDHs nanocomposite [ 25 , 26 ]. Wang et al (2018) prepared various types of lysozyme modified LDHs which exhibited excellent antibacterial activity and wound healing ability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal stability and antibacterial activity against some clinically important bacterial pathogens, namely Bacillus subtilis , Pseudomonas aeruginosa , Staphylococcus aureus , and Escherichia coli was proven for a polyacrylonitrile/Zn-Al LDHs nanocomposite [ 25 , 26 ]. Wang et al (2018) prepared various types of lysozyme modified LDHs which exhibited excellent antibacterial activity and wound healing ability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of silver combined with CFZ or NAL on the last bacterium is enhanced when the two antimicrobials are immobilized on the LDH. Indeed, the positive charge of the LDH surface is able to attract negatively charged bacterial cells by promoting bacterial adhesion on LDH, and the close contact between the antimicrobial agents and the bacteria supports the action of the active species [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above-mentioned 2D NBG antibacterial nanomaterials, some other new members of 2D nanomaterials, such as layered double hydroxides (LDHs) 213-216, laponite (Lap) 217, 218, hexagonal boron nitride (BN) 176, III 2 -VI 3 compounds (In 2 Se 3 , Bi 2 Se 3 , Sb 2 Se 3 ) 90, 177, 219, 220, and RuO 2 have also been deemed as promising antibacterial agents. For example, Wang et al prepared various morphology of lysozyme modified LDHs through tuning the ratio of cations, and found that bloom flower structure of LDHs not only could load more lysozyme but also adhere to more bacteria, which show excellent antibacterial activity and wound healing ability 175. Moreover, Ghadiri et al fabricated a Laponite/mafenide/alginate (Lap/Maf/Alg) film with remarkable antibacterial effects and good wound healing applications 221.…”
Section: 2d Nbg Antibacterial Nanomaterialsmentioning
confidence: 99%